Abusive Judicial Review: Skandal Minimum Usia dan Disfungsi Mahkamah Konstitusi - Rishan, Idul (Fakultas Hukum Universitas Jambi, 2024)
Since the adoption of the judicial review function after Indonesian democratization, it cannot be denied that the constitutional court has become an important part of the legal development in Indonesia. The Constitutional Court exists to protect and fulfill human rights. Through the function of judicial review, the Constitutional Court is used to limit the political power of the majority in parliament over the law-making process. In the case of minimum age limits for presidential and vice presidential candidates, the Constitutional Court played a strange role in conducting a judicial review. The Court, which was expected to be the last line of defense for a democratic constitutional order, then presented judicial dysfunction. This article tries to answer three things. First, identify the Constitutional Court’s abusive judicial review; second, analyze the factors driving abusive judicial review; and third, determine the impact of abusive judicial review on the Indonesian Constitutional Court. This study is doctrinal legal research. The results show that the Court has carried out abusive practices in terms of the minimum age limits for presidential and vice presidential candidates. Leadership problems, politicization of the judiciary, and weak supervision are the reasons for the growth of abusive judicial review. The impact of Constitutional Courts has damaged electoral democracy and fostered the growth of political dynasties. Abstrak Sejak pengadopsian fungsi judicial review pasca transisi politik, tak bisa dimungkiri Mahkamah Konstitusi telah menjadi bagian penting dalam konteks pembangunan hukum di Indonesia. Mahkamah Konstitusi hadir untuk memberikan perlindungan dan pemenuhan hak asasi warga negara. Melalui fungsi judicial review, Mahkamah Konstitusi diperankan untuk membatasi besarnya kekuatan politik mayoritas yang ada di parlemen atas proses pembentukan undang-undang. Dalam perkara batas minimum usia calon presiden dan wakil presiden, Mahkamah Konstitusi memperlihatkan wajah lain dalam praktik judicial review. Mahkamah yang diharapkan mampu menjadi garis pertahanan terakhir (last line of defense) bagi tatanan konstitusional demokratis kemudian mengalami disfungsi yudisial. Studi ini mencoba menjawab tiga hal: pertama, mengidentifikasi praktik penyalahgunaan kekuasaan (abusive) Mahkamah Konstitusi; kedua, faktor pendorong perilaku abusive Mahkamah; ketiga, dampaknya terhadap Mahkamah Konstitusi. Melalui studi hukum doktriner, artikel ini menunjukkan, Mahkamah melakukan praktik abusive dalam perkara batas minimum usia calon presiden (capres) dan calon wakil presiden (cawapres). Problem kepemimpinan, politisasi jabatan dan lemahnya pengawasan menjadi alasan tumbuhnya perilaku abusive mahkamah. Mahkamah Konstitusi telah merusak demokrasi elektoral dan memupuk tumbuhnya dinasti politik.